Strongly Coupled CoO Nanoclusters/CoFe LDHs Hybrid as a Synergistic Catalyst for Electrochemical Water Oxidation - Gao, Zhi‐Wen; Ma, Tian; Chen, Xue‐Min; Liu, Hui; Cui, Lan; Qiao, Shi‐Zhang; Yang, Jing; Du, Xi‐Wen (Small (Weinheim an der Bergstrasse, Germany), 2018)
Exploiting high‐performance, robust, and cost‐effective electrocatalysts for the oxygen evolution reaction (OER) is crucial for electrochemical energy storage and conversion technologies. Engineering the interfacial structure of hybrid catalysts often induces synergistically enhanced electrocatalytic performance. Herein, a new strongly coupled heterogeneous catalyst with proper interfacial structures, i.e., CoO nanoclusters decorated on CoFe layered double hydroxides (LDHs) nanosheets, is prepared via a simple one‐step pulsed laser ablation in liquid method. Thorough spectroscopic characterizations reveal that strong chemical couplings at the hybrid interface trigger charge transfer from CoII in the oxide to FeIII in the LDHs through the interfacial FeOCo bond, leading to considerable amounts of high oxidation state CoIII sites present in the hybrid. Interestingly, the CoO/CoFe LDHs exhibit pronounced synergistic effects in electrocatalytic water oxidation, with substantially enhanced intrinsic catalytic activity and stability relative to both components. The hybrid catalyst achieves remarkably low OER overpotential and Tafel slope in alkaline medium, outperforming that of Ru/C and manifesting itself among the most active Co‐based OER catalysts. A strongly coupled CoO/CoFe layered double hydroxides heterogeneous catalyst with proper interfacial structures is prepared via a one‐step laser ablation method. The strong chemical coupling at the hybrid interface triggers charge transfer through the interfacial FeOCo bond, resulting in abundant high oxidation state CoIII sites. The hybrid catalyst exhibits pronounced synergistic effects for the oxygen evolution reaction, with substantially enhanced intrinsic activity, turnover frequency, and stability.